“Didactic strategies for the development of listening and speaking applied in the teaching of the english language in the seventh-grade students of the general basic education School Ernesto Bucheli” - Zamora Moncerrate, Rosa Samantha (2022)
The main objective of this research is to establish the didactic strategies applied by English teachers to develop listening and speaking skills with 7th grade students of the General Education School "Ernesto Bucheli" in the first quarter of the 2021-2022 school year. A 10-question survey was applied to 13 seventh grade students of basic education to identify their perceptions of the different didactic strategies with respect to listening and speaking skills. The information was processed in Excel and presented in graphs. The analysis was made pointing out the main results, the concept of literature review of different authors and the researcher's point of view. On the other hand, this research was oriented with a quantitative approach of descriptive and bibliographic type to obtain better results since useful information was sought to support the research work and thus be able to describe step by step the work done, however, the data collection technique called survey whose instrument was the questionnaire with closed questions gave as a final result the lack of knowledge of the different strategies and the lack of motivation that may exist when learning a new language. In addition, there are strategies that are not taught to the students which could be useful for a better understanding of the listening and speaking skills; therefore, several recommendations were presented based on the results of the surveys to improve the teaching-learning process and thus obtain positive results. Finally, it was concluded that the Ministry of Education or the educational institution should train the English teacher about the different approaches to listening and speaking as a teaching process allowing the teacher to apply this learning in the classroom.